Autologous stem cell transplantation for enteropathy-associated T-cell lymphoma: a retrospective study by the EBMT : brief report - Jantunen, Esa; Boumendil, Ariane; Finel, Herve; Luan, Jian-Jian; Johnson, Peter; Rambaldi, Alessandro; Haynes, Andrew; Duchosal, Michel A.; Bethge, Wolfgang; Biron, Pierre; Carlson, Kristina; Craddock, Charles; et al. (Blood, 2013)
Enteropathy-associated T-cell lymphoma (EATL) is a rare subtype of peripheral T-cell lymphomas with a poor prognosis. Autologous stem cell transplantation (ASCT) was retrospectively evaluated as a consolidation or salvage strategy for EATL. The analysis included 44 patients who received ASCT for EATL between 2000 and 2010. Thirty-one patients (70%) were in first complete or partial remission at the time of the ASCT. With a median follow-up of 46 months, relapse incidence, progression-free survival, and overall survival were 39%, 54%, and 59% at 4 years, respectively, with only one relapse occurring beyond 18 months posttransplant. There was a trend for better survival in patients transplanted in first complete or partial remission at 4 years (66% vs 36%; P = .062). ASCT is feasible in selected patients with EATL and can yield durable disease control in a significant proportion of the patients.